Heat stress has divergent effects on the milk microbiota of Holstein and Brown Swiss cows - F. Ceciliani; A. Maggiolino; F. Biscarini; Y. Dadi; L. De Matos; P. Cremonesi; V. Landi; P. De Palo; C. Lecchi (Journal of Dairy Science)
ABSTRACT: Heat stress (HS) is one of the pivotal causes of economic losses in dairy industries and affects welfare and performance, but its effect on milk microbiota remains elusive. It is also unclear if and how different breeds may cope with HS in sustaining productive performance. The objectives of this study were to compare (1) the performance of 2 dairy breeds, namely Holstein and Brown Swiss, subjected to HS and (2) the different effects of HS on the milk microbiota of the 2 breeds in thermal comfort conditions and HS. The study was carried out on 36 dairy cows, 18 per breed. The HS was induced by switching off the cooling system during a natural heat wave for 4 d. In addition to the temperature-humidity index, animal stress was confirmed by measuring respiratory frequency and rectal temperature twice daily at 0400 h and 1500 h. The HS affected the 2 breeds differently. The rectal temperature increased with HS in both breeds. Milk yield recording and sampling were performed during the morning milking of d 1 (at 0400 h) and afternoon milking of d 4 (at 1700 h). Productive parameters were also different: milk yield, FCM, ECM, protein and casein content, and renneting parameters were decreased in Holstein cows but remained unaffected in Brown Swiss cows. The HS also modified the milk microbiota of the 2 breeds differently. During HS, the Brown Swiss cows had milk microbiota that was richer (α diversity) than that of the Holstein cows. Comparing the time points before and during HS within breeds showed that Brown Swiss cow milk microbiota was less affected by HS than Holstein cow milk microbiota. Under the same thermal comfort condition, milk microbiota did not discriminate between Brown Swiss and Holstein. Consistently with α and β diversity, the number of operational taxonomic units (OTU) at the genus level that changed their abundance during HS was higher in Holstein (74 OTU) than in Brown Swiss (only 20 OTU). The most significant changes in abundance affected Acinetobacter, Chryseobacterium, Cutibacterium, Enterococcus, Lactococcus, Prevotella-9, Serratia, and Streptococcus. In conclusion, the present report confirms and extends previous studies by demonstrating that Brown Swiss cows regulate their body temperature better than the Holstein breed. The relative thermal tolerance to HS compared with Holstein cows is also confirmed by changes in milk uncultured microbiota, which were more evident in Holstein cows than in Brown Swiss cows.